NGHIÊN CỨU CHẾ TẠO SẢN PHẨM CHỐNG NẤM MỐC CHO GIÀY DA QUÂN NHU TỪ NGUYÊN LIỆU QUẾ - Võ, Thị Hoài Thu; Nguyễn, Trọng Dân; Đinh, Thị Thu Trang; Nguyễn, Trường Giang; Đỗ, Thị Thuý (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON PREPARATION OF ANTI-MOULD PRODUCT FOR MILITARY LEATHER SHOES FROM CINNAMON MATERIAL This paper shows the process of preparation of an anti-mold product containing α-brom cinnamaldehyde transformed from Vietnam cinnamon oil. The obtained α-brom cinnamaldehyde in the product is confirmed by modern chemical physic methods such as: IR, 1H-NMR, 13C-NMR. 6 strains of mould on military leather shoes are isolated and identified by morphology characters. The obtained product is examined by acceleration test method. The result indicates strong inhibitory effect of α-brominated cinnamaldehyde on the development of the mould destroying military leather shoes.